Analisis Dimensi Akuntabilitas Pengelolaan Dana Desa : Studi pada Pemerintah Desa di Kecamatan Kelubagolit Kabupaten Flores Timur - Ruslan; Wisak Watawai, Wilhelmus (Insan Cita Bongaya Research Journal, 2024)
This study aims to analyze the influence of clarity of budget targets and competence of village officials on the accountability of village fund management in the Village Government in Kelubagolit District, East Flores Regency. Data collection method uses a questionnaire with a saturated sampling technique. The number of samples is 50 village officials. The data analysis method uses multiple linear regression. The results of the study show that the clarity of budget targets and the competence of village officials have a positive and significant effect on the accountability of village fund management